Game Mobile Edukasi interaktif untuk Meningkatkan Kemampuan Membaca Anak Usia Dini - Teguh Setiadi; Laksamana Rajendra Haidar (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The development of reading learning carried out at Cut Nyak Dien Kindergarten which is located at Surokonto Wetan Village, RT. 03/RW. 03 district. Pageruyung Kab. Kendal. The ongoing learning process still uses manual or conventional methods by using posters in the form of cardboard. The limited media used in learning causes teachers to need to explain repeatedly using teaching aids. When viewed from the media used, namely cardboard, the images that will be conveyed are less attractive to children in studying the images. This is because children still have difficulty in pronouncing letters and connecting pictures with words. One of the supporting factors for interactive learning is by utilizing game media for learning facilities using mobile education-based technology. The purpose of making and developing educational games is to attract children's attention to play games that function as learning media. One of them is to improve children's language skills. Language development is part of the abilities that must be possessed by children. One of the language skills that must be developed is the ability to read, because by reading children can understand the meaning of words and sentences, and understand that there is a relationship between spoken and written language. The application of educational games in classroom learning with the inquiry learning method in the simplest explanation is a form of approach that is oriented to early childhood. Where the teacher only gives direction and then students are able to realize their learning and thinking abilities. In this method, children play an active role in learning. Researchers need to solve this problem with the ADDIE method, namely by analysis, design, development, implementation and evaluation. The data collection technique is using a questionnaire. The results of the validation of interactive game development can be concluded that interactive games to improve early childhood reading skills are valid, practical, and effective